2006
DOI: 10.1111/j.1365-2958.2006.05238.x
|View full text |Cite
|
Sign up to set email alerts
|

Study of an alternate glyoxylate cycle for acetate assimilation by Rhodobacter sphaeroides

Abstract: SummaryOrganisms, which grow on organic substrates that are metabolized via acetyl-CoA, are faced with the problem to form all cell constituents from this C2-unit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
118
0
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(122 citation statements)
references
References 38 publications
1
118
0
3
Order By: Relevance
“…As the intracellular concentration of acetyl-CoA is likely to be high in cells grown on acetate and as pyruvate level should be kept low through consumption by acetolactate synthase, the net flux through this enzyme is expected to favour pyruvate synthesis when the bacteria are grown on acetate. Noticeably, the high level of acetyl-CoA can be maintained in the cell through the upregulation of acetyl-CoA transferase (Rru_A1927; fold change, 1.8; P-value, 0.004; identified peptides, 34), which could be responsible for acetate activation, as mentioned by Alber et al (2006). The preference for reductive carboxylation activity is further supported by the observation of major downregulation of all subunits of the pyruvate dehydrogenase (lipoamide) complex (Rru_A1878, Rru_A1879, Rru_A1881).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As the intracellular concentration of acetyl-CoA is likely to be high in cells grown on acetate and as pyruvate level should be kept low through consumption by acetolactate synthase, the net flux through this enzyme is expected to favour pyruvate synthesis when the bacteria are grown on acetate. Noticeably, the high level of acetyl-CoA can be maintained in the cell through the upregulation of acetyl-CoA transferase (Rru_A1927; fold change, 1.8; P-value, 0.004; identified peptides, 34), which could be responsible for acetate activation, as mentioned by Alber et al (2006). The preference for reductive carboxylation activity is further supported by the observation of major downregulation of all subunits of the pyruvate dehydrogenase (lipoamide) complex (Rru_A1878, Rru_A1879, Rru_A1881).…”
Section: Resultsmentioning
confidence: 99%
“…All the enzymes belonging to this pathway in Rb. sphaeroides have been identified, purified and extensively characterized (Alber et al, 2006;Erb et al, 2007Erb et al, , 2008Erb et al, , 2009bMeister et al, 2005). Schneider et al (2012) recently showed that Methylobacterium extorquens also employs the EMC pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, propionyl-CoA is transformed to malate, from which 1 glyoxylate and 1 acetyl-CoA are generated (20). More recently, a second hypothesis, the ethylmalonyl-CoA pathway (EMCP), was proposed from studies of C2 assimilation pathways in R. sphaeroides (21)(22)(23). This pathway ( Fig.…”
mentioning
confidence: 99%
“…Table 3) support this latter observation. Whatever the nature of the complete anaplerotic pathway (see Alber et al, 2006), the apparent malate synthase in crude extract shows the cycle to be present at high levels in the taurine(carbon)-ammoniumgrown cells, but only in traces in taurine(nitrogen)-succinate-grown cells (Table 3). Presumably, when taurine is supplying nitrogen in the presence of a C 4 carbon source in excess (in our case succinate), the anaplerotic sequence is not necessary, and is regulated independently of the operation of the taurine degradative pathway.…”
Section: Discussionmentioning
confidence: 99%